USING DIFFERENT METHODS FOR TEACHING GRAMMATICAL FEATURES OF ENGLISH INFINITIVE AND GERUND. (Journal of Universal Science Research, 2024)
This article explores the basics of infinitives and gerunds, important verb forms in English grammar. Infinitives typically start with "to," while gerunds end in "-ing" and act like nouns. Teaching these concepts involves interactive exercises, role plays, error correction, and real-life examples. By mastering infinitives and gerunds through practical techniques, learners can improve their language skills and communicate more effectively